Emerging insights into the gut microbiota as a key regulator of immunity and response to immunotherapy in hepatocellular carcinoma - Siqi Ren; Yinping Zhang; Xingyue Wang; Jiahong Su; Xiang Wang; Zijun Yuan; Xinyu He; Sipeng Guo; Yu Chen; Yu Chen; Yu Chen; Shuai Deng; et al. (Frontiers in Immunology)
The gut microbiota, a complex microbial ecosystem closely connected to the liver via the portal vein, has emerged as a critical regulator of liver health and disease. Numerous studies have underscored its role in the onset and progression of liver disorders, including alcoholic liver disease, metabolic dysfunction-associated steatotic liver disease (MASLD), metabolic dysfunction-associated steatohepatitis (MASH), liver fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). This review provides a comprehensive overview of current insights into the influence of the gut microbiota on HCC progression, particularly its effects on immune cells within the HCC tumor microenvironment (TME). Furthermore, we explore the potential of gut microbiota-targeted interventions, such as antibiotics, probiotics, prebiotics, and fecal microbiota transplantation (FMT), to modulate the immune response and improve outcomes of immunotherapy in HCC. By synthesizing insights from recent studies, this review aims to highlight microbiota-based strategies that may enhance immunotherapy outcomes, advancing personalized approaches in HCC treatment.